Endogenous firm entry in an estimated model of the U.S. business cycle - Sven Offick; Roland C. Winkler (Kiel University, Department of Economics, 2015)
A recent theoretical literature highlights the role of endogenous firm entry as an internal amplification mechanism of business cycle fluctuations. The amplification mechanism works through the competition and the variety effect. This paper tests the significance of this amplification mechanism, quantifies its importance, and disentangles the competition and the variety effect. To this end, we estimate a medium-scale real business cycle model with firm entry for the U.S. economy. The competition and the variety effect are estimated to be statistically significant. Together, they amplify the volatility of output by 8.5 percent relative to a model in which both effects are switched off. The competition effect accounts for most amplification, whereas the variety effect only plays a minor role.
Keywords: E20; E32; 330; Bayesian estimation; Business Cycles; Competition Effect; Entry; Mark-ups; Variety Effect